TEKNOLOGI SISTEM PAKAR DALAM MENDIAGNOSA BERAT BADAN LAHIR RENDAH MENGGUNAKAN CASE BASED REASONING (CBR) - Mauliza Mauliza; Defry Hamdhana (STMIK Budi Darma, 2018)
Body Weight is one indicator for health of newborns (BBL). The health of newborns is a seriously problem and one indicator for the cause of infant mortality in Indonesia. In this case, we use expert system with case based reasoning (CBR) methods to diagnosis the low birth weight. Our paper aims to knows risks factor which measurement the low birth weight and can develop the hospital system to diagnose the initial symptoms of newborns type. We use age, HB rate, parity distance, number of antenental visits, amount of parity, socio-economy status, mother’s education level, and nutrition status of pregnant while the maternal work history variable is a protection factor.Keywords: Expert System, CBS, low birth weight